Strawberry farming with lichens: an alternative to the environment | Cultivo de morangos com líquens: uma alternativa para o ambiente - Machado, José (Revista Geama, 2016)
The strawberry culture demand for labor, it requires special care to prevent pest problems. Its cultivation is characterized by indiscriminate use of pesticides, which leads researchers to seek more natural alternatives for improving soil conditions, and decreased use of chemicals. In this context, lichens can be a viable alternative, since its properties in modifying the chemical composition of the soil, addition of antimicrobial action and their insecticidal substances. The aim of work is to inform about the strawberry cultivation your climate conditions and possible use of lichens in your cultivation.